Improving Student Understanding in Animation Lessons Using Open Ended Project Based Learning Models Assisted With Augmented Reality Technology - Chandra Andriawan; Basori Basori; Astika Wulansari (Pendidikan Teknik Informatika dan Komputer, Universitas Sebelas Maret, 2023)
The competence of students in understanding and applying animation in making animated films is still low. This study aims to improve the learning outcomes of Animation lessons in class XII Film Production using the Open-Ended Project Based Learning model assisted by Augmented Reality Technology. This study used the CAR (Classroom Action Research) method, carried out in two cycles with one meeting in each cycle, consisting of planning, implementation, observation, and reflection. Data collection techniques in this study were observation, interviews, tests, and field notes. The data analysis technique used quantitative and qualitative analysis. The results in this study are the percentage of student's knowledge in the first cycle, which is 69% quite good, and in the second cycle, 74% good. The rate of student's skills in the first cycle is 80% good, and in the second cycle, 94.3% is very good. This study concludes that the Open-Ended Project Based Learning model assisted by Augmented Reality Technology can improve cognitive and psychomotor learning outcomes in Animation lessons in class XII Film Production. Kata Kunci: Animation, Augmented Reality, Open Ended Project Based Learning.